Implementasi Konsep Trias Politica dan Peradilan pada Masa Rasulullah SAW serta Khulafaur Rasyidin - Syaiful Akromi Munthe (Albayan Journal of Islam and Muslim Societies, 2025)
This study aims to examine the implementation of the concept of trias politica and the judicial system during the time of the Prophet Muhammad (peace be upon him) and the era of the Rightly Guided Caliphs, with a focus on how the principle of separation of powers was manifested in early Islamic governance. The research employs a descriptive qualitative method through library research, comparing primary sources such as the Qur’an, Hadith, and the Charter of Medina, along with relevant secondary scholarly literature. The analysis is grounded in the theory of separation of powers and the Islamic theory of justice. The findings indicate that during the Prophet Muhammad’s leadership, the concept of trias politica had not yet been formally established. Nonetheless, legislative, executive, and judicial functions were integrated within a single authority, as reflected in the Charter of Medina, which affirms his role as lawmaker, administrator, and judge. In the era of the Khulafaur Rasyidin under Caliph Umar ibn al-Khattab the governmental structure began to show a clearer delineation of powers through the establishment of a more independent judiciary and the reinforcement of procedural justice principles. In conclusion, although a formal separation of powers was not implemented during either period, both the Prophet Muhammad and the Rightly Guided Caliphs upheld fundamental values such as justice, consultation (shura), and the rule of law. These values served as the essential foundations for the development of Islamic governance.